Using applied linguistics in teaching: The role of linguistics in the English language - Ghafar, Zanyar Nathir (Yayasan Mitra Persada Nusantara, 2023)
The study aims to focus on linguistics as it relates to the instruction of the English language will be the focus of this particular piece of writing. It will discuss the role of linguistics in educating those still working on their English language skills. The literature review, often called library research, is the foundation for data analysis. The comparison technique and the descriptive approach are used throughout the data collection process. Due to the discovery, one can realize that linguistics pays attention to the part it plays in the lecture hall. The definitions of applied linguistics, as well as a development in that definition and the return of the essential subject matter to education and teaching, are presented in this article to assess language instruction through the lens of applied linguistic theory. The most recent results from research in applied linguistics conducted on language instruction are presented here. Teaching the English language is used as an example to integrate it with practical language teaching theory, allowing for the creation of relevant teaching experiments. According to the results, applied linguistic teaching theory may raise the students' desire for learning, which may boost the efficiency with which they acquire a second language. The findings show that the theory of applied linguistics should be built on language teaching, that the method of language teaching should be modified, and that improvements should be made to the information transferred to students.